Complementary and Integrative Health Knowledge and Practice in Primary Care Settings: A Survey of Primary Care Providers in the Northwestern United States. (June 2021) - Schwartz, Malaika R; Cole, Allison M; Keppel, Gina A; Gilles, Ryan; Holmes, John; Price, Cynthia
Background: The demand for complementary and integrative health (CIH) is increasing by patients who want to receive more CIH referrals, in-clinic services, and overall care delivery. To promote CIH within the context of primary care, it is critical that providers have sufficient knowledge of CIH, access to CIH-trained providers for referral purposes, and are comfortable either providing services or co-managing patients who favor a CIH approach to their healthcare. Objective: The main objective was to gather primary care providers' perspectives across the northwestern region of the United States on their CIH familiarity and knowledge, clinic barriers and opportunities, and education and training needs. Methods: We conducted an online, quantitative survey through an email invitation to all primary care providers (n = 483) at 11 primary care organizations from the WWAMI (Washington, Wyoming, Alaska, Montana and Idaho) region Practice and Research Network (WPRN). The survey questions covered talking about CIH with patients, co-managing care with CIH providers, familiarity with and training in CIH modalities, clinic barriers to CIH integration, and interest in learning more about CIH modalities. Results: 218 primary care providers completed the survey (45% response rate). Familiarity with individual CIH methods ranged from 73% (chiropracty) to 8% (curanderismo). Most respondents discussed CIH with their patients (88%), and many thought that their patients could benefit from CIH (41%). The majority (89%) were willing to co-manage a patient with a CIH provider. Approximately one-third of respondents had some expertise in at least one CIH modality. Over 78% were interested in learning more about the safety and efficacy of at least one CIH modality. Conclusion: Primary care providers in the Northwestern United States are generally familiar with CIH modalities, are interested in referring and co-managing care with CIH providers, and would like to have more learning opportunities to increase knowledge of CIH.